Kompetensi Peradilan Tata Usaha Negara Dalam Memeriksa, Mengadili Dan Memutus Perkara Nomor: 26/G/2020/Ptun.Abn - Gaspersz, Delvin; Pietersz, Jemmy Jefry; Pattipawae, Dezonda Rosiana (Jurnal Saniri, 2023)
Introduction: The grace period for filing a lawsuit is conceptually aimed at ensuring legal certainty and government stability. The State Administrative Court in examining, adjudicating and deciding cases that have passed the grace period of 90 (ninety) days as regulated in Article 55 of Law Number 5 of 1986 The issues discussed are whether the State Administrative Court can accept the lawsuit which has passed the grace period and whether the State Administrative Court has the authority to examine, hear and decide on cases Number: 26/G/2020/PTUN.ABN.Purposes of the Research: provide academic input for the development of legal science, especially in the field of Constitutional Law, State Administrative Law related to the PTUN's Competence in Examining, Judging and Deciding Cases Number: 26/G/2020/PTUN.ABNMethods of the Research:  This research uses normative legal research, case approach, statutory approach and concept approach, primary, secondary and tertiary legal materials, legal material procedures using primary legal materials which are then linked to secondary legal materials and processing and analysis of legal materials using qualitative descriptive analysis.Results of the Research: The results of the study indicate that the competence of the State Administrative Court in examining, adjudicating and deciding cases that have passed the grace period is not the authority of the State Administrative Court. The period of 90 (ninety) days to file a lawsuit to the State Administrative Court (PTUN) plays a very important role, because if the period is lapsed, the State Administrative Decision (KTUN) cannot be contested anymore even if the KTUN issued by the agency or State Administration officials are not in accordance with applicable legal procedures